The Influence Of Kanguru Treatment Method (Pmk) On Body Temperature Changes In Babies Low Birth Weight (Lbw) At Prof Dr H. M. Anwar Makkatutu Bantaeng - Asnidar; Tenriwati; Isma; Muriyati (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2023)
Background: Low birth weight (LBW) is a problem in the health sector, especially during the perinatal period. Low birth weight is a baby born not meeting normal weight, or a baby's birth weight is less than 2500 grams. which will cause infant mortality to increase during the perinatal period, where LBW babies are unable to maintain body temperature within the normal range and cause complications such as asphyxia, hypothermia, and hyperbilirubinemia, not only LBW babies will be prone to apnea and necrotizing enterocolitis which will increase risk of infant mortality. Objective: To know the effect of kangaroo care on changes in body temperature in LBW babies in the Neonatal Intensive Care Unit (NICU) Prof. Hospital. Dr. H.M. Anwar Makkatutu Bantaeng. Method: Type of quantitative research with one group pre-test and post-test pre-experiment, data analysis used using the Wilcoxon test. Research Results: Ha is accepted. That is, there is an effect of kangaroo treatment on changes in body temperature in LBW babies in the Neonatal Intensive Care Unit (NICU) Prof. Hospital. Dr. H. M. Anwar Makkatutu Bantaeng with a P-Value of 0.000, where the value of α = 0.05. Conclusions and Suggestions: Implementation of the kangaroo method can increase body temperature in LBW infants who experience hypothermia. It is hoped that mothers who have LBW babies can apply the kangaroo method at home and for agencies and services to develop the implementation of the kangaroo method.